2019
DOI: 10.3390/cancers11121828
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Ginkgetin and Resveratrol in Suppressing VEGF-Induced Angiogenesis: A Therapy in Treating Colorectal Cancer

Abstract: Ginkgetin, a biflavone from Ginkgo biloba leaf, and resveratrol, a polyphenol found in grape and wine, are two phytochemicals being identified for its binding to vascular endothelial growth factor (VEGF): the binding, therefore, resulted in the alteration of the physiological roles of VEGF-mediated angiogenesis. The bindings of ginkgetin and resveratrol were proposed on different sites of VEGF, but both of them suppressed the angiogenic properties of VEGF. The suppressive activities of ginkgetin and resveratro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…Here, RSV significantly reduced the Hb percentages of tumor mass, indicating the anti-angiogenetic effect of RSV against implanted COLO205-luc. Similar results were reported by Hu et al [25], who found a significant anti-angiogenetic effect of RSV alone or in combination with ginkgetin, a biflavone from Ginkgo biloba leaf, through the downregulation of vascular endothelial growth factor (VEGF)-mediated angiogenesis. Moreover, RSV induced apoptosis of in vivo implanted breast cancer cells (MDA-MB-231) through a significant reduction in extracellular levels of VEGF [26].…”
Section: Discussionsupporting
confidence: 87%
“…Here, RSV significantly reduced the Hb percentages of tumor mass, indicating the anti-angiogenetic effect of RSV against implanted COLO205-luc. Similar results were reported by Hu et al [25], who found a significant anti-angiogenetic effect of RSV alone or in combination with ginkgetin, a biflavone from Ginkgo biloba leaf, through the downregulation of vascular endothelial growth factor (VEGF)-mediated angiogenesis. Moreover, RSV induced apoptosis of in vivo implanted breast cancer cells (MDA-MB-231) through a significant reduction in extracellular levels of VEGF [26].…”
Section: Discussionsupporting
confidence: 87%
“…The expression levels of VEGF in the control group were higher compared to the healthy group ( Figure 8(F,G) ), indicating that corneal alkali burns increased VEGF expression, which thereby induced CNV. Resveratrol is a highly effective anti-VEGF agent against CNV (Hu et al., 2019 ). Ocular drug delivery has been a challenge due to physiological eye obstacles such as blinking and the production of tears.…”
Section: Resultsmentioning
confidence: 99%
“…This investigation also covers the down-regulation of the products of the following genes, COX-2, 5-LOX, VEGF, IL-1, IL-6, IL-8, AR and PSA [ 93 ]. This recent study also emphasized and defined the pharmacological significance of the activity of resveratrol and ginkgetin in angiogenesis, in cancer cells and its related signaling mechanisms [ 94 ]. It was found out that combining resveratrol and ginkgetin can be efficient as an angiogenesis inhibitor and has the potential characteristics of a drug for cancer treatment and drug development.…”
Section: Targets Of Resveratrol In Tumor Microenvironmentmentioning
confidence: 99%
“…This combination was found to suppress VEGF through a succeeding steps interfering with the VEGF-related signaling transduction. These activities of resveratrol and ginkgetin in comparison with other anti-angiogenesis agents, can be studied further for the treatment and prophylaxis of different types of angiogenesis-related illnesses and can be a novel angiogenesis inhibitors [ 94 ].…”
Section: Targets Of Resveratrol In Tumor Microenvironmentmentioning
confidence: 99%